ETHNOMATHEMATICAL STUDY OF THE WEDDING CULTURE OF THE MUNTAK DAYAK TRIBE - Saputri, Linda Dwi; Lestari, Kasihani; Riyanti, Vera (JME (Journal of Mathematics Education), 2025)
Research purposes: This is for now. What is the draft of mathematics that exists in the Dayak Muntak of the wedding procession ethnic group in Balai Agas Village? Research: This method employs a qualitative approach, drawing on ethnographic methods. Subject study is the chief custom in Balai Agas Village. Object study is a procession wedding ethnic group, Dayak Muntak, in Balai Agas Village, District Belimbing, Melawi Regency. Research: This involves instrument interviews and a review of the literature. The data analysis technique refers to the Miles and Huberman model, which encompasses both the data reduction process and the selection of relevant data from ethnomathematics in the context of the Dayak Vomiting ethnic group, specifically a wedding tradition. After the stage reduction is complete, researchers present the data and conclude. Based on the results of interviews, studies, and literature, the concept of mathematics in the Dayak Muntak wedding procession encompasses various concepts, numbers, and logical mathematical principles. Concept number in procession: Mantoh Adat and Beduda. Whereas draft logic mathematics, there is in process beduda, customs that are paid as well as amur boras buang taba